2017
DOI: 10.12968/jowc.2017.26.sup2.s32
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin tears in the extremities among elderly residents at a nursing home in Denmark

Abstract: The low prevalence found in this study may reflect the focus on prevention of skin tears that the nursing home has maintained over the past year. Nevertheless, the appropriate prevention and management of residents with skin tears is an ongoing challenge for health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
0
28
0
3
Order By: Relevance
“…Among patients with skin tears, the most common locations were the extremities, as described in this and three other studies (16)(17)(18). The locations also match the occurrence among patients in residential care settings (13,17,19). One author suggests that the dependent patient primarily sustains upper extremity skin tears acquired during routine activities in daily life, whilst the independent patient primarily sustains skin tears on the lower extremity, caused when transferring from wheelchairs or tub chairs (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among patients with skin tears, the most common locations were the extremities, as described in this and three other studies (16)(17)(18). The locations also match the occurrence among patients in residential care settings (13,17,19). One author suggests that the dependent patient primarily sustains upper extremity skin tears acquired during routine activities in daily life, whilst the independent patient primarily sustains skin tears on the lower extremity, caused when transferring from wheelchairs or tub chairs (20).…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected by using a data collection sheet developed for a previous study (Figure 1, Datasheet) (13). The datasheet contained demographic data and clinical information.…”
Section: Surveyors and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with a history of skin tears were nearly four times more likely to develop a skin tear at 6 months. Three previous studies reported similar outcomes, but variation in their research design and the limited quantitative analysis did not permit further evaluation . LeBlanc et al suggested that a possible relationship existed between having a history of skin tears and the occurrence of skin tears.…”
Section: Discussionmentioning
confidence: 99%
“…9 A higher value was found in a study conducted in Denmark, with a prevalence of 11.4% in 202 patients admitted at a hospital of the same level. 10 Among studies performed in long-term care facilities for the elderly, the ST prevalence found was of 3% in Belgium, 11 4.6% in Denmark, 12 11.6% in Brazil, 13 and 14.7% in Canada. 14 Some studies have indicated associations between ST occurrence and low scores in the Braden scale.…”
mentioning
confidence: 97%